Analysis of The Effect of Dynamic Capability, Knowledge Management on Employee Performance - Rina Purnama (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
This study aims to analyze the effect of Dynamic Capability on Knowledge Management, analyze the effect of Dynamic Capability on Employee Performance, and to analyze the effect of Knowledge Management on Employee Performance in SINOTRUK companies. The data analysis technique used is the Structural Equational Modeling (SEM) method, the method of collecting data using a questionnaire to employee SINOTRUK. Sampling technique using purposive sampling method with a sample size of 120 respondents. Based on the results of the study it can be concluded that Dynamic Capability has on positive effect on Knowledge Management, Dynamic Capability has a positive effect on Employee Performance, and Knowledge Management also has a positive effect on Employee Performance.